New records of Leopardus guigna tigrillo and Lycalopex culpaeus in Placilla de Peñuelas, Chile and threats to their conservation - Guzmán Marín , Byron Cristian; José-González, María; Palma, Nelson; Guerrero, Jimena; Muñoz Peña, Patricio (Therya Notes, 2022)
The kodkod (Leopardus guigna) is considered vulnerable by the International Union for Conservation of Nature. On the other hand, although the Andean fox (Lycalopex culpaeus) is considered as least concern in Chile, the protected areas it inhabits are not enough to maintain viable populations. Here, we contribute to the knowledge of the Chilean fauna and identify threats to its conservation through camera traps. Three camera traps were placed in the study area, which remained active for 2 months. Whenever activated, cameras recorded time / temperature and 30 s videos. The presence of the kodkod, subspecies tigrillo (L. g. tigrillo) was recorded in the study area through photographs and videos. Additionally, the presence of Andean fox (L. culpaeus) and evidence of anthropogenic activities were recorded. We highlight the presence of L. g. tigrillo, an endemic species recorded for first time in the study area, and that of L. culpaeus. We detected anthropogenic activities (illegal logging, cattle grazing, motocross) that may represent a threat to the survival of these carnivores. We propose specific conservation actions to protect these species and their habitat.